Strengthening the pipeline: a leadership communication and organizational culture model to engage, retain and advance early-career women - LaGree, Danielle; Olsen, Katie (My University, 2026)
Abstract Purpose – This study examines the organizational entry phase of the socialization process as an opportunity for organizations to communicate culture through leadership empowerment behaviors to retain and advance young talent, particularly young women. Design/methodology/approach –In-depth interviews with 31 early-career women explored their journeys from recruitment through their first year of full-time employment, highlighting the significance of cultural fit, organizational culture, socialization processes and leadership empowerment behaviors. Findings – Organizational socialization and culture conveyed via leadership empowerment behaviors are undoubtedly intertwined, working in tandem to effectively acclimate young women, helping them understand the meaningfulness of their work and ultimately supporting their visions and paths to future leadership and successful tenure at their organizations. Practical implications – This study offers a practical phase model that outlines strategies organizations should implement at four distinct time periods within the first year of a newcomer's employment Originality/value – This study was inspired by organizational leaders' desires to engage young workers and effectively acclimate them to the workplace. It is the first study of its kind to effectively combine multiple theoretical perspectives of organizational life–socialization, culture and leadership empowerment–to address strategies for improved employee acclimation.
Keywords: Organizational culture; Organizational socialization; Leadership empowerment; Leadership communication; Career development; Onboarding; Female leadership; Early-career; Young workers; Gen Z